Dimethyl fumarate therapy suppresses B cell responses and follicular helper T cells in relapsing-remitting multiple sclerosis. (August 2019) - Holm Hansen, Rikke; Højsgaard Chow, Helene; Sellebjerg, Finn; Rode von Essen, Marina
Background: Dimethyl fumarate (DMF) is a disease-modifying therapy used for patients with relapsing-remitting multiple sclerosis (RRMS). B cells are important contributors to the pathogenesis of RRMS, where they regulate the inflammatory immune responses and participate in development of lesions in the central nervous system (CNS). The impact of DMF on B cell subpopulations remains incompletely understood. Objectives: In this study, we evaluated the effects of DMF on B cell subpopulations and their effector functions. Methods: Blood from 21 DMF-treated and 18 untreated patients with RRMS was analyzed by flow cytometry. Results: We found that DMF reduces the frequency of circulating antigen–experienced B cells, a reduction likely related to a reduced frequency of follicular helper T (TFH ) cells and an increased frequency of follicular regulatory T (TFR ) cells. Studying the impact of monomethyl fumarate (MMF), the primary metabolite of DMF, on B cell effector function in vitro showed that MMF increased the frequency of transforming growth factor (TGF)-β-producing B cells and decreased the frequency of B cells secreting lymphotoxin (LT)-α, tumor necrosis factor (TNF)-α, interleukin (IL)-6, and to a lesser extent IL-10. Conclusion: In summary, these data suggest an anti-inflammatory role of DMF and its metabolite MMF on the B cell compartment.